Enhancing Financial Behavior through Financial Awareness and Professional Advice: Insights from the Government Sub-sidized Housing Program for Lecturers in Medan - Sabaruddin Chaniago; Amin Hou; Adi Harianto; Septa Diana Nabella; Ibrahim Mallam Fali (Journal of Business Integration Competitive, 2026)
This study seeks to examine the impact of financial awareness on financial behavior, utilizing financial advisers as a mediating variable among Generation Y lecturers in Medan City participating in the government's 3 million subsidized housing program. The consistently poor quality of financial decision-making about subsidized housing ownership underscores the necessity of enhancing financial literacy, facilitated by the involvement of competent financial counselors. This research utilized a quantitative methodology, namely a survey technique including the dissemination of questionnaires to participants. The study's population comprised Generation Y lecturers in Medan City, with a sample size of 78 individuals selected through a random sampling method. The analysis of data was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to evaluate both direct and indirect correlations among variables. The findings indicated that financial awareness exerted a favorable and significant influence on financial behavior. Moreover, financial awareness substantially affected the utilization of financial advisors, which subsequently yielded a favorable impact on financial behavior. It was shown that financial advisors indirectly affected the link between financial knowledge and financial conduct. This research underscores the necessity for government and subsidized housing program administrators to incorporate financial literacy initiatives tailored to the distinct requirements of lecturers, including training in long-term financial planning, subsidized mortgage simulations, and financing risk management. Additionally, it is recommended that higher education institutions offer internal financial consulting services or partner with financial advising organizations to aid instructors in making prudent and sustainable financial choices. This study shows that banks and other financial institutions need to strengthen the role of financial advisors by using education and personalized services to improve the way customers handle their money, especially when it comes to subsidized housing financing programs